Siglec-15 Promotes Tumor Progression in Osteosarcoma via DUSP1/MAPK Pathway - Fan, Meng-ke; Zhang, Guo-chuan; Chen, Wei; Qi, Li-li; Xie, Ming-fang; Zhang, Yue-yao; Wang, Ling; Zhang, Qi (Frontiers in Oncology, 2021)
Recurrence and metastasis are critical features of osteosarcoma (OS) that cause its poor prognosis. Sialic acid-binding immunoglobulin-like lectin 15 (Siglec-15) gene overexpression has been detected in various cancers. However, the expression and function of Siglec-15 in OS remain unclear. In our studies, we proved that downregulation of Siglec-15 decreased the proliferation, migration and invasion of OS cells by inducing epithelial-mesenchymal transition (EMT) in vitro and in vivo. Conversely, Siglec-15 overexpression promoted the growth, migration and invasion of OS cells. We then identified a number of differentially expressed genes in Siglec-15-silenced cells by RNA-Seq analysis. Among them, dual-specificity phosphatase 1 (DUSP1/MKP1) was significantly downregulated. DUSP1 overexpression promoted the proliferation, migration and invasion of Siglec-15-knockdown OS cells. In addition, we used Western blotting to show that DUSP1-mediated inhibition of p38/MAPK and JNK/MAPK expression was attenuated when Siglec-15 expression was inhibited, suggesting that Siglec-15 promotes the malignant progression of OS by suppressing DUSP1-mediated suppression of the MAPK pathway. Moreover, we used immunohistochemistry to show that both Siglec-15 and DUSP1 were highly expressed in OS tissues. High Siglec-15 expression was associated with tumor lung metastasis, and high DUSP1 expression was associated with the tumor Enneking stage. Kaplan-Meier analysis showed that the overall survival rate in the high Siglec-15 expression group was lower than that in the low Siglec-15 expression group. Pearson analysis showed a positive correlation between Siglec-15 and DUSP1 expression in OS tissues. These data show that Siglec-15 expression promotes OS development and progression by activating DUSP1 and may be a novel target for OS treatment.